Towar an educational transmedia proposal. User profile and digital platforms interaction for students of private technological school of higher education Toulouse Lautrec - Huamán-Huillca, Melissa (2022)
With the intention of developing an educational digital proposal to generate meaningful learning experiences, it was decided to work with transmedia narrative. To that end, as an initial phase, it was required to identify the digital ecosystem of the students and to profile its users. This current research objective is to analyze the student’s interaction on the various digital platforms on social media by the Toulouse Lautrec Private Higher Technological School, specialized in creative careers. Based on quantitative and descriptive level approach, data was collected through a survey whose participants were the students. Additionally, a review and analysis of both educational and transmedia narrative experiences were created. This allowed us to conclude that the most suitable platforms are YouTube, Facebook, Whatsapp, Pinterest, among others. In addition, it was concluded that for the desired student interaction, it is necessary to interconnect and proportion the educational content in relation with the stages of learning and the continual commitment of the students.